Odpowiedzi

2010-02-07T12:30:44+01:00
C) x-4/5=0.8
x=0,8+4/5
x=0,8+0,8
x=1,6

d) 6i 1/8y=1
49/8y=1 /:49/8
y=1*8/49
y=8/49

e) -2,2+x=6,1
x=6,1+2,2
x=8,3

f) -1/3y=10 /:(-1/3)
y=10*(-3)
y=-30

g) 8a+4=36
8a=36-4
8a=32 /:8
a=4

h) 8/9k+1/3=3
8/9k=3-1/3
8/9k=8/3 /:8/9
k=8/3*9/8
k=3

i)6b-3=-9
6b=-9+3
6b=-6 /:6
b=-1

j) -3/4-1/4l=2.25
-1/4l=2,25+3/4
-0,25l=2,25+0,75
-0,25l=3 /:(-0,25)
l=-12

k) -2.5c-8=17
-2,5c=17+8
-2,5c=25 /:(-2,5)
c=-10

l) 0.4m-2=-6
0,4m=-6+2
0,4m=-4 /:0,4
m=-10
2 5 2
2010-02-07T12:31:41+01:00
C) x-4/5 = 0.8
x = 4/5 + 0.8
x = 08 + 0.8
x = 1.6
e) -2.2+ x = 6.1
x = 6.1 - (-2.2)
x = 8.3
f) -1/3y = 10
y = 10 : - 1/3
y = 10 *- 3/1
y = -30
g) 8a + 4 = 36
8a = 36 - 4
8a = 32
a = 32 : 8
a = 4
h ) 8/9k + 1/3 =3
8/9k = 3 - 1/3
8/9k = 2 2/3
k = 2 2/3 : 8/9
k = 8/3 * 9/8
k = 3
i)6b - 3 = -9
6b = -9 + 3
6b = -6
b = -6 : 6
b = -1
j) - 3/4 - 1/4l = 2.25
-0.75 - 0.25l = 2.25
0.25l = 2.25 - (-0.75)
0.25l = 3
l = 3 : 0.25
l = 12
k) -2.5c -8 = 17
-2.5c = 17 +8
-2.5c = 25
c = 25 : -2.5
c = - 10
l )0.4m - 2 = -6
0.4m = -6 + 2
0.4m = -4
m = -4 : 0.4
m = -10
1 5 1
2010-02-07T12:35:08+01:00
Rozwiąż równanie
c) x-4/5=0.8
x-0,8=0,8
x=0,8+0,8
x=1,6

d) 6i 1/8y=1
49/8y=1
y=1*8/49
y=8/49

e) -2,2+x=6,1
x=6,1+2,2
x=8,3

f) -1/3y=10
y=10:(-1/3)
y=10*(-3)
y=-30

g) 8a+4=36
8a=36-4
8a=32
a=4

h) 8/9k+1/3=3
8/9k=3-1/3
8/9k=2 i 2/3
8/9k=8/3
k=8/3*9/8
k=3

i)6b-3=-9
6b=-9+3
6b=-6
b=-1

j) -3/4-1/4l=2.25
-1/4l=2,25+3/4
-1/4l=2,25+0,75
-1/4l=3
l=4:(-1/4)
l=4*(-4)
l=-16

k) -2.5c-8=17
-2,5c=17+8
-2,5c=25
c=25:(-2,5)
c=-10


l) 0.4m-2=-6
0,4m=-6+2
0,4m=-4
m=-4:0,4
m=-10